Analysis of Difference Variable Parameter Effect to Temperature Drop: Application of Cooling Tower - Uwe, Lizzybel Pawun; Mohd Salleh, Zuliazura (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This abstract presents a comprehensive overview of the piping system before entering cooling tower that has been specifically engineered to enhance the operational efficiency of a cooling tower. The piping system plays a vital role in connecting the cooling tower with different components, facilitating the continuous flow of water to efficiently dissipate heat. The piping system consists of a complex arrangement of interconnected pipes, heat exchangers and valves that facilitate the movement of water from the tower to the relevant equipment. The engineering of the piping system entails meticulous consideration of its design and layout to maximise cooling performance while simultaneously minimising pressure losses and energy consumption. In order to ensure the variable that gives better performance, the elevation of pipes and different temperature inlets are to be considered in this research. The 3D piping model involves a pipeline from the setpoint of the heat exchanger to the cooling tower. The model part includes the pipe and flange drawn using Solidworks. According to the parameter, the elevation of the pipe will change to get the optimum result for the data analysis. The simulation results show that the longer the elevation of the pipe, the lesser the velocity flow in the pipeline, which affects the pressure distribution in the pipeline, and the pressure decreases due to the elevation of the pipe. The simulation results show that higher velocity occurs on the inlet pipe rather than the outlet of the pipe when different temperature inlets are applied. However, different temperature inlets did not affect the pressure distribution along the pipeline as the results indicate no significant difference between the different temperature inlets for each model.